2013
DOI: 10.1097/ccm.0b013e31827ca637
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy for the Critically Ill in the ICU

Abstract: Physical therapy in the ICU appears to confer significant benefit in improving quality of life, physical function, peripheral and respiratory muscle strength, increasing ventilator-free days, and decreasing hospital and ICU stay. However, further controlled trials of better quality and larger sample sizes are required to verify the strength of these tentative associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
276
6
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(315 citation statements)
references
References 58 publications
11
276
6
13
Order By: Relevance
“…and 2 meta‐analysis 436, 448. These results revealed that implementation of early‐stage rehabilitation interventions resulted in significantly improved motor function, 6‐min walk distance (6MWD), and shortened artificial respiration periods.…”
Section: Cq18: Icu‐acquired Weakness (Icu‐aw) and Post‐intensive Carementioning
confidence: 91%
“…and 2 meta‐analysis 436, 448. These results revealed that implementation of early‐stage rehabilitation interventions resulted in significantly improved motor function, 6‐min walk distance (6MWD), and shortened artificial respiration periods.…”
Section: Cq18: Icu‐acquired Weakness (Icu‐aw) and Post‐intensive Carementioning
confidence: 91%
“…However, not only MRC‐SS but also skeletal muscle strength, functional exercise capacity, and ADL gradually improved in 2 months. An increased awareness on the potential influence and benefit of early rehabilitation in the ICU has been noted worldwide, and previous reports support EM and physical therapy as safe and effective interventions with a potential significant effect on functional outcomes 9. Despite physiotherapy in the ICU appears to contribute significant benefit, its effect in patients with ICU‐AW remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lagerung hingegen bedeutet die Veränderung von Körperpositionen mit dem Ziel der Einwirkung auf schwerkraftbedingte Effekte [3,45,57,63].…”
Section: Frühmobilisationunclassified
“…Maßnahmen zur Mobilisation werden in drei Bereiche eingeteilt: die passive Mobilisation, die assistierte aktive Mobilisation und die aktive Mobilisation [3,31,32,49,57,63,77,89] …”
Section: Elemente Der Mobilisationunclassified